Human Capital in the Tourism and Hospitality Industry: A bibliometric approach - Durão, Marília (2025)
Human capital is a prolific research topic in tourism and hospitality, given its decisive role in this industry’s competitiveness, sustainable growth and development. This chapter contributes to the current theoretical understanding of human capital in the tourism and hospitality field through thematic knowledge mapping. This study adopts a bibliometric analysis using VOSviewer software to examine 451 studies published from 2008 to 2023, retrieved from the Scopus database. Emerging themes, leading authors and academic institutions were mapped using co-citation and keyword co-occurrence analyses. Five clusters were identified within the human capital research landscape, including business outcomes, economic growth, tourism development, models of human capital development and technology. The results show that human capital research in hospitality and tourism has gained momentum in recent years and is expanding.